Load Forecasting in the Context of Global Covid-19 Vaccination Using Facebook Prophet - Barevan, Kevinaldo; Halim, Abdul (JURNAL NASIONAL TEKNIK ELEKTRO, 2022)
Forecasting the electrical energy load is a very important initial stage in the operation of the electricity system so that the system works reliably, stably, and economically. The load forecasting process is carried out in the range of hours to years. This study focuses on short-term load forecasting (STLF) where in general the effects of weather conditions and human activities are very influential. In this study, we will study further the effects of the Covid-19 pandemic, namely the number of vaccines and the level of community mobility on changes in electrical loads. The study of the effect of the vaccine is the new point of this research. In electrical load forecasting, the revised Facebook Prophet method will be used. This revision is intended so that the effects of the pandemic can be included in the model. To test the effectiveness of the proposed model, a case study of the Pennsylvania electrical load data was carried out. In 2021 with the addition of the vaccination variable, the MAPE value is 15.26%. The amount of data used could possibly affect the forecasting process and MAPE results. So, the MAPE value is quite good when compared to other studies.